Diagnostic criteria of the state of the distributed brain stem regulatory structures in cerebrovascular diseases - Pogorelov A.V. (Medičnì Perspektivi)
The clinical-neurophysiological study of 62 patients with history of subtentorial ischemic stroke was carried out in order to determine the criteria of dysfunction of morphologically distributed stem regulatory structures. It was revealed that these disorders are sustainable with the possibility of recourse and influence on the course of stroke. It was marked the influence of this disorders on the levels of consciousness, severity of state, recovery rate, asthenia level, sleep function. Manifestations of cerebral cardiac syndrome, impaired attention, orientation reaction, speed of sensomotoric acts are also marked. Patients with these disorders have low rates of recovery of functions. Neurophysiological criteria of these disorders are the lack of expressive reactions in electroencephalography, reduction of their overall level, instability of rhythm - generating structures and others.